Some Bernstein-type inequalities for trigonometric polynomials - Babenko, V. F.; Ligun, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The refinements of some well-known Bemstein-type inequalities for trigonometric polynomials are obtained.